Comercialización de servicios turísticos y diversidad cultural en la comunidad Tolte-pistishí, cantón Alausí, provincia de Chimborazo - López Guerrero, Christian Javier (2024)
BSTRACT: The present research project was carried out in the province of Chimborazo, canton Alausí, Tolte-Pistishí community, with the aim of analysing the relationship between the marketing of tourist services and cultural diversity. The main problem is the misuse of cultural diversity, the limited promotion of attractions and services, the lack of marketing mechanisms for products and inadequate organizational management. In this context, methods were employed such as, the type of descriptive research, to detail the current situation of the community, correlation research to find the relationship between the study variables; on the other hand, the mixed research design, since community opinions were received; non-experimental because the variables were not manipulated at the time of conducting the research; finally, the cross-design that was carried out over a certain period of time. To the objectives of the research work, the data were interpreted, processed and discussed through two Likert-scale questions surveys. The results of the analysis of the Chi-square hypothesis test revealed that tourist services are not effectively integrated with local culture, this deficiency is attributed to the lack of accommodation options, restaurants and activities that adequately reflect the culture of the community. According to the findings, it was considered essential to design a handbook for the design of tourist products with a cultural focus in the Tolte-Pistishi community, with the aim of creating and planning meaningful attractive experiences for visitors and the local population.